Dynamic, reversible oxidative addition of highly polar bonds to a transition metal - Bertermann, Ruediger; Boehnke, Julian; Braunschweig, Holger; Dewhurst, Rian D.; Kupfer, Thomas; Muessig, Jonas H.; Pentecost, Leanne; Radacki, Krzysztof; Sen, Sakya S.; Vargas, Alfredo (Journal of the American Chemical Society, 2016)
The combination of Pt complexes and indium trihalides leads to compounds that form equilibria in solution between their In X oxidative addition (OA) products (Pt indyl complexes) and their metal-only Lewis pair (MOLP) isomers (LnPt -> InX3). The position of the equilibria can be altered reversibly by changing the solvent, while the equilibria can be reversibly and irreversibly driven toward the MOLP products by addition of further donor ligands. The results mark the first observation of an equilibrium between MOLP and OA isomers, as well as the most polar bond ever observed to undergo reversible oxidative addition to a metal complex. In addition, we present the first structural characterization of MOLP and oxidative addition isomers of the same compound. The relative energies of the MOLP and OA isomers were calculated by DFT methods, and the possibility of solvent-mediated isomerization is discussed.

Deoxygenative hydroboration of primary and secondary amides: a catalyst-free and solvent-free approach - Kumar, Rohit; Bisai, Milan Kumar; Jain, Shailja; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2021)
In contrast to the recent reports on catalytic hydroboration of amides to amines with pinacolborane (HBpin), a simple catalyst-free and solvent-free method for the hydroboration of a variety of amides has been realized. To get the mechanistic insights, DFT calculations have been performed.

Diverse reactivity of carbenes and silylenes towards fluoropyridines - Kundu, Gargi; Ajithkumar, V. S.; Bisai, Milan Kumar; Tothadi, Srinu; Das, Tamal; Vanka, Kumar; Sen, Sakya S. (Chemical Communications, 2021)
The reaction of IDipp with C5F5N led to functionalization of all three carbon atoms of the imidazole ring with HF2- as the counter-anion (1). Reactivity with 2,3,5,6-tetrafluoropyridine gives only C-F bond activation leaving C-H bonds intact (5b). The reaction of SIDipp with C5F5N in the presence of BF3 afforded the ring cleavage product (3). Analogous reactions with silylene led to oxidative addition at the Si(II) center.

Diverse reactivity of hypersilylsilylene with boranes and threecomponent reactions with aldehyde and HBpin - Bisai, Milan Kumar; Swamy, V. S. V. S. N.; Raj, K. Vipin; Vanka, Kumar; Sen, Sakya S. (Inorganic Chemistry, 2021)
The recently reported hypersilylsilylene PhC-(NtBu)(2)SiSi(SiMe3)(3) (1) reacts with BH3, 9-BBN, and PhBCl2 to yield the respective Lewis acid base adducts 2-4, respectively. Compound 4 undergoes isomerization to form a ring expansion product 5. The same silylene was found to initially form an adduct with HBpin (6) and subsequently isomerized to 7 via the rupture of the B-H bond of HBpin (7), where the hydride was bound to the carbon atom of the amidinate ligand and the Bpin unit was attached to the silicon center. Surprisingly, the reaction of 1 with HBcat results in PhC(NtBu)(2)Bcat (8). Subsequently, we have shown that HBcat forms the same product when it reacts with related silylene PhC(NtBu)(2)SiN(SiMe3)(3) (1'). With all of these reactions in hand, we ponder if silylene can activate two small molecules at one time. In this work, we delineate the three-component reactions of silylenes 1 and 1' with 4-fluorobenzaldehyde and HBpin, which afforded unusual coupling products, 9 and 10, respectively. Note that 9 and 10 were prepared from the cleavage of the B-H and C=O bonds by silylene in a single reaction and are the first structurally attested Si-C-O-B coupled products.

Development of six-membered saturated cyclic diaminocarbenes in main-group chemistry - Kundu, Gargi; Sen, Sakya S. (Dalton Transactions, 2025)
In recent years, there has been a remarkable surge in the utilization of saturated N-heterocyclic carbenes (NHCs) as ligands in main group chemistry. While the field has predominantly focused on five-membered NHCs and cyclic alkyl(amino) carbene (CAAC) ligands, the investigation of six-membered NHCs (6-NHCs) has only just begun. Despite possessing higher nucleophilicity than their five-membered counterparts, 6-NHCs have been less explored due to their lack of structural rigidity. This feature article aims to highlight recent developments in 6-NHCs in only main group chemistry. Exciting new studies have demonstrated the activation of B-H bonds in HBpin, ring expansion from a six-membered to a seven-membered ring under ambient conditions, and the stabilization of transient units ``H-B 00000000 00000000 00000000 00000000 11111111 00000000 11111111 00000000 00000000 00000000 O'' and ``(OH)BO'', among other intriguing phenomena. A major focus of this review is on synthetic approaches for 6-NHC-stabilized main-group compounds and their unusual properties, as revealed by spectroscopic and crystallographic data. While the chemistry of 6-NHCs is still in its nascent stage, the findings presented in this feature article underscore the need for its exploration and further investigation. Furthermore, this review provides valuable insights into effective synthetic methods for creating new 6-NHCmain group (B, Al, Si, P, Zn, etc.) complexes, along with mechanistic explanations for some of these reactions. These advances hold great promise for the future development of this exciting and rapidly evolving field of N-heterocyclic carbene chemistry.